Default-risky Sovereign Debt - Andreas Wiggers (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
Not only corporate but also sovereign debtors, in particular developing countries, may get into financial difficulties. Contrary to corporate issuers, they decide themselves if they continue to fulfill their debt obligations or convert their debt. I analyze the value of a default-risky sovereign bond in a setting in which foreign trade is reduced in case the country does not fulfill its obligations. Comparing the costs of debt service with the value of the punishment via foreign trade, the country voluntarily decides when to reorganize its debt. Knowing this threshold the value of a sovereign coupon-bond can be calculated.
Keywords: G15; G33; F34; H63; 330; Credit risk; sovereign debt; endogenous default; Internationale Anleihe; Länderrisiko; Wertpapieranalyse; Umschuldung; Sanktion; Theorie